Wpływ autostrady A4 na strategie rozwoju i planowanie przestrzenne w gminach na przykładzie regionu opolskiego - Słodczyk, Janusz; Klimek, Renata (The Impact of the A4 Motorway on Local Development Strategies and Spatial Planning on the Example of the Opole Region, 2006)
The A4 motorway (Zgorzelec-Korczowa), being one of the four elements of 3ld Pan-European Transport corridor, is very important in terms of its economic and social impact on neighboring areas. The A4 is located in the south of Poland. The large amounts of goods and passengers that are transported over the A4 make the areas adjacent to the motorway junctions attractive for investment in transport-related services and other economic activities. The purpose of the paper is to present the impact of the A4 motorway on spatial development in the municipalities located in its neighborhood. The spatial policy of the Opole region as described in the provincial spatial development plans, spatial policy of municipalities as described in local development strategies and actual changes in spatial development were analyzed. One of the main conclusions is that many municipalities are planning investment sites and that the A4 motorway has been the driving force behind major policy changes for most of them. However, two years after finishing the construction of the A4 in the Opole region, actual investment is small and no "development axis" can be identified along the motorway.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 96-106